Appropriate implantable cardioverter-defibrillator interventions in cardiac resynchronization therapy–defibrillator (CRT-D) patients undergoing device replacement: time to downgrade from CRT-D to CRT-pacemaker? Insights from real-world clinical practice in the DECODE CRT-D analysis. Issue 9 (27th November 2017) - Narducci, Maria Lucia; Biffi, Mauro; Ammendola, Ernesto; Vado, Antonello; Campana, Andrea; Potenza, Domenico Rosario; Iori, Matteo; Zanon, Francesco; Zacà, Valerio; Zoni Berisso, Massimo; Bertini, Matteo; Lissoni, Fabio; et al.
Abstract: Aim: Ventricular tachycardia (VT)/ventricular fibrillation (VF) occurrence after cardiac resynchronization therapy–defibrillator (CRT-D) replacement is unknown; hence, there is no practical guideline to recommend either CRT-D or CRT-pacemaker at the time of device replacement. We observed the 1-year VT/VF occurrence after CRT-D replacement in a subanalysis of the Detect Long-term Complications after ICD Replacement (DECODE) registry. Methods and results: A total of 332 consecutive patients who had undergone CRT-D replacement from 2013 to 2015 were enrolled in 36 Italian centres. The primary endpoint was the number of patients with any appropriate implantable cardioverter-defibrillator (ICD) interventions during 12-month follow-up. The secondary endpoint comprised death from any cause and appropriate ICD interventions. At replacement, 214 (64.5%) patients had a left ventricular ejection fraction ≤ 35% and 138 (41.6%) patients had a secondary prevention indication for ICD. Seventy (21.1%) patients had no longer indication to ICD therapy. During a median follow-up period of 406.5 (362–533) days, VT/VF requiring therapy delivery occurred in 57 (17%) patients, specifically in 7% of those who no longer had an ICD indication. On multivariate analysis, number of criteria for ICD replacement independently predicted appropriate ICD intervention during follow-up [hazard ratio (HR) = 1.62, 95% confidence interval (CI) 1.07–2.46; log-rank P  = 0.02]. The combined endpoint of death from any cause or appropriate ICD therapy occurred in 76 (23%) patients. Only NYHA class remained associated with this combined endpoint (HR = 1.97, 95% CI 1.23–3.14; P  = 0.005). Conclusions: The DECODE registry showed the 'real-world' experience of CRT-D recipients approaching device replacement, in which 7% of patients who no longer had an indication for ICD therapy experienced appropriate ICD interventions.